Factors That Cause Students Reluctant to Speak English at STKIP Tomakaka Tiwikrama - Taufan, Muhammad Ybnu; Damier, Wahyunida (Jurnal Ilmiah Multidisiplin Amsir, 2024)
This research tried to find out factors that cause students reluctant to speak English at STKIP Tomakaka Tiwikrama. Reluctance to speak can cause difficulties in a student’s life as troubling in expressing her opinion and troubling in giving information to the other. In the condition of understanding a factor causing reluctance, the students to speak is an alternative to solving the event. The objective of this research is to find out factors that cause students reluctant to speak English at STKIP Tomakaka Tiwikrama. This study used a qualitative approach because it generated the data through the use of instruments such as field notes and transcriptions from observations and interviews. This study also used data from observation and interviews from students in STKIP Tomakaka Tiwikrama Academic year 2020 and 2021. After conducting this research entitled “The factors that cause the students‟ reluctance to speak English at STKIP Tomakaka Tiwikrama” some conclusions can be drawn. Based on the data analysis from the research, it could be concluded that there are two factors of students'‟ reluctance to speak English at STKIP Tomakaka Tiwikrama. The first one was the language factor, namely: pronunciation, vocabulary and grammar. The second one was psychological factors, which are: lack of confidence, shyness, anxiety and motivation.